IMF Staff papers, Volume 45 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1998)
This paper describes the issue of corruption around the world. The paper surveys and discusses issues related to the causes, consequences, and scope of corruption, and possible corrective actions. It emphasizes the costs of corruption in terms of economic growth. It also emphasizes that the fight against corruption may not be cheap and cannot be independent from the reform of the state. If certain reforms are not made, corruption is likely to continue to be a problem regardless of actions directly aimed at curtailing it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet